Do Hot Hands Exist among Hedge Fund Managers? An Empirical Evaluation - JAGANNATHAN, RAVI; MALAKHOV, ALEXEY; NOVIKOV, DMITRY (Journal of Finance, 2010)
ABSTRACT In measuring performance persistence, we use hedge fund style benchmarks. This allows us to identify managers with valuable skills, and also to control for option‐like features inherent in returns from hedge fund strategies. We take into account the possibility that reported asset values may be based on stale prices. We develop a statistical model that relates a hedge fund's performance to its decision to liquidate or close in order to infer the performance of a hedge fund that left the database. Although we find significant performance persistence among superior funds, we find little evidence of persistence among inferior funds.